Mayan rainforest farming - Weitzel, Hans-Ernst (Oley, PA : Bullfrog Films, 1983)
Tropical rainforests are being decimated, but there are still a few'solares,' or orchards, where Mayan farmers continue a sustainable form of rainforest agriculture. They grow a variety of vegetables and non-food crops beneath their fruit-trees
Copy in DVD Format
VHS Format
Keywords: Rain forests -- Mexico; Orchards -- Mexico; Cropping systems -- Mexico; Sustainable agriculture -- Tropics